Effect of Experimental Pneumococcal Meningitis on Respiration and Circulation in the Rabbit - Sears, Malcolm R. (1974)
Pathophysiological studies in bacterial meningitis in man have been limited by clinical variability and the necessity for immediate therapy. After the development of a reliable animal model of pneumococcal meningitis, we studied respiration and circulation in 25 anesthetized New Zealand white rabbits during untreated pneumococcal meningitis and in 33 healthy controls. In meningitis, we found increased lactic acid in cerebrospinal fluid (CSF). Increased ventilation, perhaps due to CSF lactic acid accumulation, resulted in respiratory alkalosis; the concomitant lowering of Pco(2) acted as a homeostatic mechanism to restore pH toward normality in the CSF. Hyperventilation increased with the duration of the illness. Cardiac output was also increased with decreased peripheral vascular resistance but with only slight reduction in mean systemic and pulmonary arterial pressures. In the final hour of life, peripheral vascular resistance fell further; ventilation declined and then abruptly ceased while cardiac activity continued. Lactic acid accumulation in the CSF, found in both experimental and human pneumococcal meningitis, may cause the hyperventilation found in this disease and may contribute to death.